Deburring Method of Aluminum Mould Produced by Milling Process for Microfluidic Device Fabrication - Kushendarsyah Saptaji; Farid Triawan; Tong Keong Sai; Asmelash Gebremariam (Indonesian Journal of Science and Technology, 2021)
The existence of top burrs in micro-scale features produced by milling process can deteriorate the surface quality of a product. Ductile metals, such as aluminum alloys, are prone to suffer from top burrs formation after a slot-milling process. A brief review on the state-of-the-art of burr removal process in micro-scale milling is provided in this paper. Various deburring methods were reportedly able to remove the burrs in micro-scale features, however a much simpler method is still needed. In the present work, a deburring process by stainless steel end brushing is introduced for aluminum mould used in microfluidic device fabrication. The micro-scale features are produced by slot-milling process followed by the deburring process. The deburred moulds are then visually observed using optical microscope and Scanning Electron Microscope (SEM) and the average surface roughness and its features profile are measured using 3D Laser Scanning Confocal Microscope. As a result, the proposed deburring method can successfully remove the top burrs, as indicated by a height reduction of about 21% due to the removal action by the brush. Hence, a burr-free embossing mould with complex shape channel features can be produced by milling and by applying a simple deburring process using stainless steel end brush.